2018
DOI: 10.1093/isq/sqy020
|View full text |Cite
|
Sign up to set email alerts
|

Default Positions: What Shapes Public Attitudes about International Debt Disputes?

Abstract: This article examines public opinion toward sovereign debt disputes. Using evidence from multiple surveys fielded in Argentina-the country at the center of the most prominent legal dispute with foreign bondholders-we examine the sources of public support for debt repayment. Our evidence shows that economic self-interest and competing issue frames have little impact on attitudes toward debt repayment in Argentina. Individuals' opinions toward debt disputes are driven primarily by their longstanding symbolic att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 60 publications
1
9
0
1
Order By: Relevance
“…This sheds light on, for example, the unpopularity of currency devaluations, or why, as Argentine Economic Minister Domingo Cavallo put it, Argentineans loved the currency board in the 1990s. Second, in line with a burgeoning thread of research, we also provide micro‐level evidence that—contrary to some expectations—monetary and currency policy concerns can be salient in individuals’ minds and political behavior (Ahlquist et al., 2018; Nelson & Steinberg, 2018; Steinberg & Nelson, 2019).…”
Section: Introductionsupporting
confidence: 71%
“…This sheds light on, for example, the unpopularity of currency devaluations, or why, as Argentine Economic Minister Domingo Cavallo put it, Argentineans loved the currency board in the 1990s. Second, in line with a burgeoning thread of research, we also provide micro‐level evidence that—contrary to some expectations—monetary and currency policy concerns can be salient in individuals’ minds and political behavior (Ahlquist et al., 2018; Nelson & Steinberg, 2018; Steinberg & Nelson, 2019).…”
Section: Introductionsupporting
confidence: 71%
“…But recent work shows that things may not be so simple. For example, voters’ opinions over trade, monetary, and financial policies are often weakly held and correlate with identity concerns, ideological attitudes, or partisan commitments at least as strongly as with purported material self‐interest (e.g., Ahlquist and Levi ; Bechtel, Hainmueller, and Margalit ; Mansfield and Mutz ; Nelson and Steinberg ). Studies of policy preferences in the face of economic and financial crisis similarly suggest that both material and nonmaterial factors “matter” (e.g., Fernández‐Albertos and Kuo ; Goldstein and Peters ; Margalit ).…”
Section: External Shocks and Domestic Politicsmentioning
confidence: 99%
“…See, for instance, Abdelal, Blyth, andParsons, 2010). 26 16 Lienau's insights predate important research by Nelson and Steinberg (2018), which shows that longstanding symbolic attitudes rather than economic self-interest drove citizens' views on default in Argentina in . Nelson (2014 has also shown that ideological orientation can affect lending and borrowing practices.…”
Section: Notesmentioning
confidence: 96%